Urinary Ferritin as an Early Indicator of Tubular Injury in Diabetic Kidney Disease: Insights from NHANES and Clinical Cohorts - Huang B; Ding X; Wen W; Ye S (Diabetes, Metabolic Syndrome and Obesity)
Bin Huang,1,* Xiangyu Ding,2,* Wenjie Wen,3 Shandong Ye1 1Department of Endocrinology, The First Affiliated Hospital of USTC, Division of Life Science and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China; 2First Clinical Medical College, Anhui Medical University, Hefei, Anhui, 230001, People’s Republic of China; 3School of Stomatology, Wannan Medical College, Wuhu, Anhui, 241002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shandong Ye, Department of Endocrinology, The First Affiliated Hospital of USTC, Division of Life Science and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China, Email 981257013@qq.comObjective: To investigate the association between iron metabolism disorders and diabetic kidney disease (DKD) and to evaluate the potential of urinary ferritin as an early marker of tubular injury in diabetic patients.Methods: This study utilized data from 1,306 diabetic patients and 1,306 propensity score-matched non-diabetic controls from the NHANES (2017–March 2020) dataset. Diabetic participants were classified into Non-DKD (n = 923) and DKD (n = 383) groups based on the urinary albumin-to-creatinine ratio (UACR). Binary logistic regression and restricted cubic spline models were used to evaluate the association between iron metabolism indicators and DKD risk. Additionally, renal tissue samples from 12 patients (6 with T2DM and 6 non-diabetic controls) undergoing nephrectomy were analyzed for iron accumulation and tubular injury markers. Clinical data from 35 T2DM patients (with and without DKD) and 20 matched healthy controls were included to assess urinary ferritin and tubular injury markers. Finally, 120 T1DM patients were stratified by disease duration to assess correlations between urinary ferritin and renal injury biomarkers.Results: Decreased serum iron (OR = 0.962, P = 0.037) and increased serum ferritin (OR = 1.001, P = 0.024) were identified as independent risk factors for DKD. Diabetic patients exhibited higher renal iron, urinary ferritin, and tubular injury markers, with significant correlations between renal iron and urinary ferritin levels. Urinary ferritin levels also increased with T1DM duration, significantly correlating with tubular injury markers.Conclusion: Impaired iron metabolism, characterized by low serum iron and high serum ferritin, is an independent risk factor for DKD. Urinary ferritin may serve as a biomarker of early tubular injury in diabetic patients, even in the absence of albuminuria.Keywords: iron metabolism, diabetic kidney disease, tubular injury, urinary ferritin